Definition and Diagnosis of the Trigeminocardiac Reflex: A Grounded Theory Approach for an Update - Meuwly, Cyrill; Chowdhury, Tumul; Sandu, Nora; Golanov, Eugene; Erne, Paul; Rosemann, Thomas; Schaller, Bernhard (Frontiers in Neurology, 2017)
Background The trigeminocardiac reflex (TCR) is defined as sudden onset of parasympathetic dysrhythmias including hemodynamic irregularities, apnea, and gastric hypermotility during stimulation of sensory branches of the trigeminal nerve. Since the first description of the TCR in 1999, there is an ongoing discussion about a more emergent clinical definition. In this work, the author worked out an approach to such an improved definition. Methods In this study, a grounded theory approach was used. Literature about TCR was systematically identified through PubMed (MEDLINE), EMBASE (Ovid SP) and ISI Web of Sciences databases from 1/2005 until 8/2015. TCR was defined as a drop of heart rate (HR) below 60 bpm or 20% to the baseline. A grounded theory approach was used to analyze and interpret the data through a synthesis by the researcher's perspectives, values, and positions. Results Out of the included studies, the authors formed available data to an update of the understanding of changes in hemodynamic parameters (HR and blood pressure) in a TCR. According to this update, an HR deceleration should be a constant observation to identify a TCR-episode while a drop in blood pressure should probably not being fixed to a certain percentage of decrease. Conclusions The here presented working definition improves our understanding of the TCR. It leads the way to a new understanding of the TCR for a proper clinical definition.